Criminal behavior and mental disorders: systematic review of self-report instruments for adolescents in conflict with the law - Pomahuacre Carhuayal, Juan Walter (2022)
Adolescent criminal behavior is a problem that can be approached from different angles.  One of the most relevant is its association with symptoms of mental disorders.  Therefore, adequate and timely detection of clinical features is imperative.  In this context, self-report instruments are frequently used, even though their use has not been systematized. The present study reviews empirical articles where clinical characteristics of adolescents in conflict with the law have been evaluated with self-report instruments. Four databases (Scopus, Web of Science, PubMed and SciElo) with articles published between 2015 and 2021 and written in English, Portuguese and Spanish were reviewed.  The final selection was 30 articles.  The review highlights the use of the Youth Self Report to assess various clinical symptoms, in addition to the Youth Psychopathic Trait Inventory and the Inventory of Callous-Unemotional Traits to measure aspects linked to psychopathy.